THE NATURAL-LEGAL DIMENSION OF A PERSON’S STATUS - Píry Martin (Электронное приложение к Российскому юридическому журналу, 2019)
The natural law theory of a person as a substance of his own is presented in the article. The author analyzes historical and contemporary theories and states that any human rights and freedoms can be derived only from such a fundamental level, that a human represents an inherent nature himself. For this basic legal personality the quality of persons’ life, race, nationality, gender, and other characteristics are not decisive.